HUBUNGAN PENGETAHUAN AKSEPTOR KB SUNTIK 3 BULAN DENGAN PERILAKU PENANGANAN EFEK SAMPING DI WILAYAH KERJA PUSKESMAS SETONO - Adelia Putri Yuniardi; Hery Ernawati; Siti Munawaroh; Metti Verawati; Yayuk Dwirahayu (Universitas Muhammadiyah Ponorogo, 2022)
The success indicator of the family planning program is determined by the quality of service, one of which is the provision of quality counseling to both old and new acceptors. If counseling that can give knowledge to dissenters is lacking, it can cause problems one of the following is bad manners to manage birth control side effects. A growing knowledge of side effects can promote a positive attitude in dealing with those side effects (Yuliari, 2019). This study aims to determine the relationship between knowledge of 3-month injection family planning acceptors and the behavior of handling side effects. The research used is the analytic correlation with cross-sectional approach model. The population in this study is all 3-month injector birth control in the Wilaya Kerja Puskesmas Setono of the January - July as many as 900 participants with a monthly average of 129 patients. The large sample used as many as 32 responders. The sampling technique used is Purposive Sampling. This research data collection USES a questionnaire. Data processing techniques use editing, coding, scoring, and tabulating. Data analysis uses the chi-square ).The results of the research by testing the relationship with Chi-Square showed that at a significant level of 0.05 the correlation was obtained with a probability number of P-Value Chi-Square = 0.005. The significant value of the two variables is 0.005 0.05, which means that P-Value Chi-Square (Ho is rejected and Ha is accepted), so it can be concluded that there is a relationship between knowledge of 3 months injectable family planning acceptors and behavior in handling side effects in the Wilayah Kerja Puskesmas Setono.